2018
DOI: 10.1021/acs.jpca.8b04501
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Effect of Carbon Dioxide on Reaction OH + CO → H + CO2 in Supercritical Environment: Master Equation Study

Abstract: We investigated the reaction rates of OH + CO → H + CO in supercritical CO environment with and without additional CO molecule included in reactive complex. Ab initio potential energy surfaces previously reported a lower activation barrier and hence a catalytic effect of additional CO molecule. Here we solve the steady-state unimolecular master equations based on the Rice-Ramsperger-Kassel-Marcus theory (RRKM) and compare the rates for the two mechanisms. We found that the alternative reaction mechanism become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…We found that at higher CO 2 pressures (300 atm) and lower temperatures (below 313 K), the reaction R2 becomes faster than reaction R1, due to the fact that PRCs are present at sufficient concentrations. These findings are consistent with our previous work on autocatalytic effects in the OH + CO → H + CO 2 reaction . The effect of carbon dioxide on OH + CH 2 O reaction would be important in liquid CO 2 at room temperature, but not for oxy‐combustion processes.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We found that at higher CO 2 pressures (300 atm) and lower temperatures (below 313 K), the reaction R2 becomes faster than reaction R1, due to the fact that PRCs are present at sufficient concentrations. These findings are consistent with our previous work on autocatalytic effects in the OH + CO → H + CO 2 reaction . The effect of carbon dioxide on OH + CH 2 O reaction would be important in liquid CO 2 at room temperature, but not for oxy‐combustion processes.…”
Section: Discussionsupporting
confidence: 92%
“…Both C 6 H 6 and PC128 contain six heavy atoms in the planar or nearly planar hexagonal arrangement. This collision model was used to successfully describe pressure dependence on reactive system of a similar size in the past . The buffer gas used was CO 2 in both cases.…”
Section: Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations